To determine the correct table reflecting \( g(x) = -f(-x) \), we first need to understand the relationship between the original function \( f(x) = 2(x + 22) \) and its transformed version \( g(x) \).
- Reflection across the y-axis (\( -x \)): This means we will evaluate \( f(-x) \).
- Reflection across the x-axis: After that, to find \( g(x) \), we will negate the result of \( f(-x) \).
To see how these transformations work, let's start with some example values to create the table based on reflection about the origin.
Assuming we have a table for \( f(x) \):
| x | f(x) | |------|--------| | 1 | 2 | | 2 | 0 | | 3 | -2 |
Now let's compute \( g(x) = -f(-x) \):
-
For \( x = 1 \):
- \( f(-1) = f(1) = 2 \) (from table)
- So, \( g(1) = -f(-1) = -2 \)
-
For \( x = 2 \):
- \( f(-2) = f(2) = 0 \) (from table)
- So, \( g(2) = -f(-2) = 0 \)
-
For \( x = 3 \):
- \( f(-3) = f(3) = -2 \) (from table)
- So, \( g(3) = -f(-3) = 2 \)
This gives us the following table for \( g(x) \):
| x | g(x) | |------|--------| | 1 | -2 | | 2 | 0 | | 3 | 2 |
Now, when we compare this with the options given, the answer would be:
x | g(x)
1 | -2
2 | 0
3 | 2
This matches the table:
x g(x)
1 −2
2 0
3 2
So, the correct response is:
x g(x) 1 -2 2 0 3 2